The effects of vibration on fringe projection systems - Bointon, Patrick; Todhunter, Luke; Stavroulakis, Petros; Clare, Adam; Leach, Richard (2018)
Mechanical vibration noise is a significant source of error in precision measuring instruments. Errors due to vibration can be detected in measurement signals, and so methods to control mechanical vibration must be considered throughout the design process. Fringe projection (FP) is a fast, non-contact and non-destructive measurement technology, that allows for the rapid form measurement of engineering components. There is an increasing demand in industry for low-intervention, factory-friendly FP systems. Vibration is reported to be a significant source of mechanical error in FP measurements, and so in order to design an effective metrology solution, it is vital to first understand the FP systems’ sensitivity to vibrational noise. In this research, a methodology for assessing the effects of vibration on the measurement accuracy and repeatability of a low-cost FP system is presented. The research includes a theoretical investigation of the effects of vibration on FP measurements using a computational simulation technique, as well as an experimental study, which is compared with the simulated results. The methodology presented here allows for the rapid benchmarking of a given FP system operating in any configuration, and can be used to define the required vibrational performance parameters of the system.